Optical gas sensing: a review - Hodgkinson, Jane; Tatam, Ralph P. (IOP Publishing, 2013)
The detection and measurement of gas concentrations using the characteristic optical absorption of the gas species is important for both understanding and monitoring a variety of phenomena from industrial processes to environmental change. This study reviews the field, covering several individual gas detection techniques including non-dispersive infrared, spectrophotometry, tunable diode laser spectroscopy and photoacoustic spectroscopy. We present the basis for each technique, recent developments in methods and performance limitations. The technology available to support this field, in terms of key components such as light sources and gas cells, has advanced rapidly in recent years and we discuss these new developments. Finally, we present a performance comparison of different techniques, taking data reported over the preceding decade, and draw conclusions from this benchmarking.
Keywords: sensors; IR spectrometers; UV/vis spectrometers; fibre optic instruments; laser spectroscopy; optical and dielectric properties of gases